A perspective on high‐entropy two‐dimensional materials. Issue 1 (1st March 2022) - Cui, Yanglansen; Zhang, Yongzheng; Cao, Zhenjiang; Gu, Jianan; Du, Zhiguo; Li, Bin; Yang, Shubin
Abstract: In past decades, high‐entropy (HE) materials, containing five or more elements with approximately equal atomic ratio, are extensively investigated due to their desirable properties in a series of applications. Recently, HE two‐dimensional (2D) materials have become promising materials, which not only endow the advantages from their bulk form but also exhibit unusual properties due to their 2D features. So far, the HE 2D transition metal carbides (MXenes), dichalcogenides (TMDs), hydrotalcites (LDHs), and oxides have been successfully synthesized and performed well in different electrochemical reactions, which is originated from the synergistic effect of multicomponents and atomic thin characteristics. Here, the challenges on processing, characterization, and property predictions of HE 2D materials are emphasized. Finally, viable strategies, advanced processing, fundamental understanding, in‐depth characterization of new HE 2D materials are proposed. Abstract : High‐entropy (HE) two‐dimensional (2D) materials have emerged as novel materials, which exhibit synergetic advantages of HE and atomic thin layer. Here, the unique properties of HE 2D materials are categorized and utilized for different applications. Furthermore, various strategies, advanced processing, fundamental understanding, in‐depth characterization on future development of HE 2D materials are given.